2013
DOI: 10.1371/journal.pone.0058671
|View full text |Cite|
|
Sign up to set email alerts
|

The Probiotic Mixture VSL#3 Accelerates Gastric Ulcer Healing by Stimulating Vascular Endothelial Growth Factor

Abstract: Studies assessing the effect and mechanism of probiotics on diseases of the upper gastrointestinal tract (GI) including gastric ulcers are limited despite extensive work and promising results of this therapeutic option for other GI diseases. In this study, we investigated the mechanisms by which the probiotic mixture VSL#3 (a mixture of eight probiotic bacteria including Lactobacilli, Bifidobacteria and Streptococcus species) heals acetic acid induced gastric ulcer in rats. VSL#3 was administered orally at low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 37 publications
1
58
0
1
Order By: Relevance
“…Young and aged rats were subdivided into 2 groups: those which were given VSL#3 (CD Investments s.r.l, Rome, Italy) at the dose of 12.86 bn living bacteria/kg/day [29] in maple syrup (90–160 µl) for 6 weeks [young VSL#3-treated (YV) and aged VSL#3-treated (AV)] and control rats which received only maple syrup [young control-treated (YC) and aged control-treated (AC)]. Experiments started at day 0 and ended after 6 weeks (day 42).…”
Section: Methodsmentioning
confidence: 99%
“…Young and aged rats were subdivided into 2 groups: those which were given VSL#3 (CD Investments s.r.l, Rome, Italy) at the dose of 12.86 bn living bacteria/kg/day [29] in maple syrup (90–160 µl) for 6 weeks [young VSL#3-treated (YV) and aged VSL#3-treated (AV)] and control rats which received only maple syrup [young control-treated (YC) and aged control-treated (AC)]. Experiments started at day 0 and ended after 6 weeks (day 42).…”
Section: Methodsmentioning
confidence: 99%
“…Different strains of the lactic acid bacteria (LAB), and particularly some Lactobacillus spp., are representing some of the most commonly used probiotics, defined as "live microorganisms which, when administered in adequate amounts, confer a health benefit on the host" (Food and Agriculture Organization [FAO], and World Health Organization [WHO], 2002). Extensive research has been performed on the efficacy of various Lactobacillus strains on gastric ulcers (Dharmani et al, 2013;Khoder et al, 2016) either as single therapeutic agents or in combination with antibiotics (Boltin, 2016;Goderska et al, 2018). The majority of the investigated strains have been shown to inhibit or protect the gastric mucosal barrier through the up-regulation of prostaglandin E2 (Uchida and Kurakazu, 2004;Gotteland et al, 2006;Lam et al, 2007;Uchida et al, 2010), enhancement of mucus secretion (Gomi et al, 2013) or the regulation of inflammatory responses (Konturek et al, 2009;Şenol et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, live microorganisms serving as probiotics are of benefit to peptic ulcers. As reported, the probiotic mixture VSL#3 (including Lactobacilli, Bifidobacteria and Streptococcus species) healed acetic acid induced GU in rats by increasing the expression and production of angiogenesis promoting growth factors, primarily vascular endothelial growth factor [25]. And Lactobacillus gasseri OLL 2716 could accelerate the healing of GU, which significantly influenced gastric erosive lesions and enhanced the generation of gastric mucosal prostaglandin E2 [26].…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, when indomethacin was coadministered with broad-range antibiotics or antimicrobials, J Gastrointestin Liver Dis, June 2016 Vol. 25 No 2: 139-146 experimental animals did not develop gastric ulcers (GU) [10][11][12]. Some studies have suggested that H. pylori competitively inhibited other microbiota such as Lactobacillus acidophilus and Bifidobacterium bifidum in gastric mucosa in vivo and in vitro [13,14].…”
Section: Introductionmentioning
confidence: 99%